KAJIAN POTENSI DAN STRATEGI IMPLEMENTASI AGROFORESTRI DI SEMPADAN SUNGAI PESANGGRAHAN - Asnur, Paranita; Aisyah, Aisyah; Wiseno, Elbi; Gunarto, Thomas Yuni; Suryanto, Doddy Ari (Jurnal Bakti Masyarakat Indonesia, 2025)
The Pesanggrahan River riparian zone holds significant potential for development as an agroforestry area that supports environmental conservation and ecology-based agrotourism. However, the area faces several challenges, including the absence of clearly defined boundaries, environmental degradation caused by human activities, and a lack of appropriate plant species recommendations for sustainable development. This Community Service Program (PkM) aims to assess the existing conditions of the area, conduct boundary mapping, and provide recommendations for agricultural and forestry plant species that support both ecological conservation and economic value for local communities. The methods used in this program include site surveys to identify vegetation conditions, soil characteristics, and environmental issues; territorial mapping using drones and manual boundary marking; and interviews with local communities and stakeholders to understand their perceptions and needs regarding agroforestry and agrotourism. The results indicate that the area has already been planted with various forest trees and fruit-bearing plants, such as acacia, durian, jackfruit, avocado, and banana, as well as agricultural crops like cassava and vegetables. Additionally, boundary mapping was conducted twice to determine the designated working area for a more structured implementation of agroforestry. Based on the findings, it is recommended to implement an agroforestry system by planting forest trees and perennial fruit crops along the riverbanks to reduce erosion and strengthen the riparian ecosystem. The implementation of agroforestry is expected not only to contribute to environmental conservation but also to create economic opportunities through agrotourism and community empowerment. The success of this program requires further coordination between local governments, academics, and communities to ensure the sustainable management of the Pesanggrahan River riparian zone.